2011
DOI: 10.1007/s11060-011-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of extracranial metastasis from glioblastoma multiforme

Abstract: Extracranial metastasis is a unique but rare manifestation of glioblastoma multiforme. It is thought to arise from glioblastoma cells disseminated into the blood stream. We undertook a comprehensive analysis of 88 cases of extracranial glioblastoma (5 were gliosarcomas) published between 1928 and 2009. Cases included in the analysis were primary or secondary glioblastomas that subsequently invaded organs outside the brain or spinal cord. The median age was 38 years and the median overall survival time was 10.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
199
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(227 citation statements)
references
References 57 publications
(21 reference statements)
8
199
0
1
Order By: Relevance
“…A recently published meta-analysis of 88 cases of extracranial GBM between 1928 and 2009 demonstrated that the prognosis is particularly poor in this subset of patients, with a median survival from metastasis to death of 1.5 months; however, there has been a progressive prolongation of this interval of 0.7 months per decade between 1940 and 2000 (9). Patients treated with surgery, radiation, chemotherapy and cerebrospinal fluid (CSF) shunting exhibit the longest average survival interval from metastasis to death.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis of 88 cases of extracranial GBM between 1928 and 2009 demonstrated that the prognosis is particularly poor in this subset of patients, with a median survival from metastasis to death of 1.5 months; however, there has been a progressive prolongation of this interval of 0.7 months per decade between 1940 and 2000 (9). Patients treated with surgery, radiation, chemotherapy and cerebrospinal fluid (CSF) shunting exhibit the longest average survival interval from metastasis to death.…”
Section: Introductionmentioning
confidence: 99%
“…Younger patients exhibit an increased risk of extraneural involvement due to prolonged survival (15,17). The most common sites of extracranial metastases from glioblastoma are the lungs, bone (bone marrow), lymph nodes and soft tissues (14). This is the second report of an extracranial metastasis with a retromaxillary localization, exhibiting rapid growth and completely filling the buccal cavity.…”
Section: Discussionmentioning
confidence: 87%
“…The natural history of glioblastomas that metastasize to organs outside the central nervous system is largely unknown. Between 1928 and 2009, 88 cases of extracranial metastasis from glioblastoma (n=83) and gliosarcoma (n=5) have been published, reported and analyzed by Lun et al (14). In 2015, Pietschmann et al reviewed existing data and performed a new meta-analysis with 150 cases (15).…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. Beauchesne's comment [1] regarding our work on extracranial glioblastoma [2] and, hereby, address the issues raised by him. First, the following search terms were used in the selection of published literature: (i) extracranial glioblastoma, and (ii) extracranial metastasis glioblastoma.…”
Section: To the Editormentioning
confidence: 91%